PENGARUH CHLORHEXIDINE CHIP PADA PERAWATAN PERIODONTAL: SEBUAH META – ANALISIS - Olivia Nauli Komala; Trijani Suwandi (B-Dent: Jurnal Kedokteran Gigi Universitas Baiturrahmah, 2021)
Introduction: Chlorhexidine in mouthwash or gel is used as an adjunct therapy for periodontal treatment but the effect of using chlorhexidine chip in 3 months was unclear. Objective: The present study aimed to evaluate the effect of chlorhexidine chip on reduction of pocket depth and clinical attachment level gaining in patients with periodontitis. Methods: The literature search was done in PUBMED for the use of chlorhexidine chip as an adjunct to scaling and root planing in improving periodontal status, especially pocket depth and clinical attachment level in periodontitis patients within 3 months. The risk of bias was estimated for each study based on the Cochrane Handbook for Systematic Review of Interventions. Meta-analysis was conducted for reduction of pocket depth and gain of clinical attachment. Results: Electronic search provided 51 records and 5 studies were included. The meta-analysis indicated that there was a significant difference in reduction pocket depth (p<0.05; I2 = 97%) and gain of clinical attachment level between chlorhexidine chip plus SRP and SRP alone (p<0.05; I2 = 98%). The mean difference of reduction of pocket depth was 0.26 (0.13 – 0.40) mm and the mean difference of gain of clinical attachment level was 0.31 (0.14 – 0.47) mm. All studies had fair quality based on AHRQ standards. Conclusions: Chlorhexidine chip can be an adjunct therapy for periodontal treatment to improve the clinical condition in periodontitis patients.